Urban politics and school reform the case of Baltimore. - Orr, Marion (1996)
"Relatively little is known about the remarkable increase in the use of special districts for urban service delivery. The author assesses the utility of four alternative theoretical perspectives on the uneven use of districts in metropolitan areas. Empirical analysis of district patterns in more than 300 metropolitan areas in 1987 reveals multiple influences on district use. Local government structure and legal factors emphasized by institutional-reform and metropolitan-ecology perspectives are especially important relative to the service-demand factors asserted by public-choice and critical political-economy perspectives. Of particular note are different motivations associated with use of different geographic and financial subtypes of districts"
Keywords: Educational change - United States; Municipal government - United States; Local government